Aspek Bayi Tabung dan Sewa Rahim Ditinjau Perspektif Hukum Islam dan Hukum Positif - Muhamad Wahyudin (Formosa Journal of Sustainable Research, 2022)
Having children is the purpose of marriage to continue the offspring and inheritance of the property of both parents. However, sometimes these goals cannot be achieved in accordance with the desired expectations. So then some of them get children by means of IVF programs and rent the wombs of other women. The results obtained in the position of parents as law against children from IVF and uterine rental in a marriage bond in the perspective of Islamic and positive law, the position of inheritance of children from IVF and uterine rental in a marriage bond in the perspective of Islamic law and positive and Position of Nasab Born Through IVF and Rent a Rahim in a Marriage Bond in the Perspective of Islamic Law and Positive